Impact Of International Public Sector Accounting Standards Adoption On Accountability In Public Sector Financial Reporting In Nigeria - Duenya, Mosess I.; Upaa, Jocelyn U.; Tsegba, Ioraver N. (Archives of Business Research, 2017)
This study examined the effect of adopting International Public Sector Accounting Standards (IPSAS) on accountability in public sector financial reporting in Nigeria, using the perceptions of accounting personnel (AP), academics (AA, and auditors (AU). A sample of 130 respondents was drawn from a population of 193 AU, AP, and AA within Benue State. The Chi- Square goodness of fit test, Kruskal Wallis H test, Mann-Whitney U test, and Cohen effect size were used in data analysis. The study found that IPSAS adoption in Nigeria would improve accountability and decision making in the public sector. The study also found that significant differences existed between AP, AA and AU on the effect of IPSAS adoption on Nigeria’s public sector financial accountability. The study, therefore, recommended that the Federal Government should not relent towards IPSAS implementation in Nigeria since they would enhance accountability and decision making. Furthermore, concerted efforts should be made by the federal, state and local governments to educate the populace on what IPSAS entails in terms of financial accountability in the public sector.